Outcomes of leaflet-shaped acellular dermal matrix with a thickness-gradient for abdominal fascial defect repair in muscle-sparing TRAM flap-based breast reconstruction - Joseph Kyu-hyung Park; Seungjun Lee; Eun Joo Yang; Chan Yeong Heo; Jae Hoon Jeong; Yujin Myung (Asian Journal of Surgery, 2023)
Background: Numerous fascial closure techniques have been used to reduce donor site morbidities after transverse rectus abdominis myocutaneous (TRAM) flap harvest. A leaflet-shaped acellular dermal matrix (ADM) with a thickness gradient was designed to cover the defect effectively and to withstand the pressure applied to the lower portion of the defect. The complication and functional recovery rates of the donor site of the custom ADM were compared with those of previous methods of fascial closure (primary closure and polypropylene mesh assisted closure). Materials and methods: A retrospective review of patients undergoing immediate or delayed breast reconstruction using muscle-sparing TRAM flaps was performed. Abdominal bulging, hernia, wound dehiscence, infection, seroma, and hematoma rates were compared. The Back Performance Scale measured four months postoperatively was compared to evaluate the donor site's recovery rate. Results: A total of 173 patients were analyzed. The three groups did not differ in hernia, wound dehiscence, infection, and hematoma rates. However, the abdominal bulging rate was lower in the primary closure group, while the seroma rate was higher in the mesh group. Functional recovery was the fastest in the custom ADM group. Conclusion: A thickness-gradient, leaflet-shaped ADM can be effectively used as an onlay graft to cover the abdominal fascial defect, with similar complication rates, while providing a faster recovery of abdominal function.